Konsep Pendidikan Menurut Ibnu Miskawih: (Transformasi Antara Filsafat dan Agama) - Mahfudhi, Anas (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2016)
Speaking of education, we can not get away with philosophical thinkers, because they are the first to raise the theory of human consciousness to understand and understand its life. Indeed in the end many educational theories emerge from figures who are not from the philosophers, but the framework of thinking used can not be separated from the framework of philosophical thinking. So it is no wonder that philosophy is called the mother of Science. In this case Muslim educators generally agree that the theory and practice of education (read) Islam must be based on a basic conception of man. Discussion around this issue is something that is vital in education. Without clarity about this concept education will be groping. Even according to Ali Ashraf, Islamic education can not be clearly understood without first understanding the Islamic interpretation of the full development of the individual.